IRSIEC Technique-Integral Revision, In Semester Examination and Evaluation of Content/Course - Mulla, Ansar A.; Patil, Satyajit R.; Mulla, Taufiq (Journal of Engineering Education Transformations, 2019)
In this paper a new active learning method is discussed, IRSIEC - Integral Revision, In Semester Examination and Evaluation of Content/ Course. Method of revision, examination and assessment is done. This method can be implemented to any class of UG/PG programs. Group formation in class, instructions are given to the student, topic for each group is given with drawing sheets for presenting their topic on it. Monitor/Teacher observes and assesses students. Revision, examination and Assessment are done simultaneously. Implementation of this method requires less time and more student involvement is possible. Each student revises the content and is examined; he/she is given full chance to expose his/her learning skills. This technique has enhanced students learning compared to traditional way of teaching learning method.